Evaluation of phytochemical, physicochemical parameters and HPTLC fingerprints of different extracts of Nil Aweriya (Indigofera tinctoria L.) leaves grown in Sri Lanka. - Hapuarachchi, S.D.; Silva, D.; Kodithuwakku, N.; Perera, P.K. (ASIAN JOURNAL OF PHARMACOGNOSY, 2020)
The present study was aimed at developing several tools in proper identification, authentication and maintenance of quality control standards of raw materials of I. tinctoria. Leaf extracts were obtained following cold maceration with methanol, acetone and hot soxhlet extraction with distilled water. Each extract was subjected to phytochemical, physicochemical tests and High Performance Thin Layer Chromatography (HPTLC). Saponins were detected only in the aqueous extract while carbohydrates and reducing sugars were detected only in the methanol extract. With regard to physicochemical parameters; ash values, loss on drying, extractability and florescence analysis were determined. Values of total ash, acid insoluble ash, water soluble ash contents and loss on drying were 10.683±0.104% w/w, 0.7±0.14 % w/w, 0.925±0.035 % w/w, 3.17±0.422% w/w respectively. Extractability in each solvent; methanol, acetone and hot water were 29.536±10.29 % w/w, 12.93±0.622 % w/w and12.789±2.84 % w/w accordingly. According to florescence analysis; methanol extract was yellowish brown and pale yellow, acetone extract was brownish green and brownish yellow while aqueous extract was greenish black and intense green under day light and UV light respectively. HPTLC was run at wavelength 254 nm for each extract which was considered the preliminary tool in ascertaining the authenticity of I. tinctoria. Normal phase HPTLC profile of methanol extract showed 10 peaks with the Rf values;-0.06, -0.03, 0.00, 0.03, 0.09, 0.33, 0.63, 0.73, 0.84 and 0.86 for the solvent system; ethyl acetate : toluene : nhexane : chloroform in 2 : 2 : 4 : 2 proportion while 10 peaks were obtained for the acetone extract with the solvent system; ethyl acetate : toluene : n-hexane : chloroform in 2.5 : 2.5 : 4 : 1 proportion in which the Rf values were -0.19, -0.05, 0.04, 0.10, 0.19, 0.39, 0.52, 0.58, 0.61 and 0.81. Reverse phase HPTLC was run for the aqueous extract with the solvent system; methanol : distilled water: ethanol in 3 : 3 : 5 proportion which showed 13 peaks with the Rf values; 0.06, 0.12, 0.14, 0.16, 0.22, 0.30, 0.37, 0.39, 0.47, 0.50, 0.75, 0.84 and 0.87. Since, many Ayurveda formulations contain I. tinctoria as an ingredient, above parameters and HPTLC fingerprints can be used for the proper identification and authentication of the raw materials excluding the counterfeit or sub standard materials leading to safety, quality and efficacy of the manufactured Ayurveda preparations.
Keywords: Indigofera tinctoria L.; fingerprints; physico-chemical; phytochemical; high performance thin layer chromatography